POTRET DINAMIKA KEHIDUPAN MASYARAKAT DESA BOJONG CATANG, SERANG-BANTEN - Maryani, Maryani; Saffa, Agista (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2024)
ABSTRACT The portrait of the dynamics of the Bojong Catang Village community is a description of the life of a village community that is still thick with religious norms and customary law, whose economic needs depend on natural livelihoods. The purpose of this research is to find out the life and development that occurs from time to time in the village of Bojong Catang. The method used in this research is descriptive qualitative. Data collection used interview and observation techniques with the village head, RT and villagers, then documentation. The results showed that Bojong Catang village has a diversity of life dynamics, such as local culture that is still maintained, the main source of livelihood by utilizing natural resources. There are significant changes in life in the community, there are also Bojong Catang Village programs, community migration/urbanization, and local languages are also still preserved in everyday life.